FAKTOR YANG MEMPENGARUHI KEPUTUSAN TRANSFER PRICING PERUSAHAAN MANUFAKTUR DI BEI (2019–2023) - Rismatul hasana; Yuniorita Indah Handayani; Wiwik Fitriya Ningsih (RISTANSI: Riset Akuntansi, 2025)
The purpose of this study is to examine the partial and simultaneous effects of taxes, tunneling incentives, bonus mechanisms, company size, and exchange rates on transfer pricing practices within manufacturing firms listed on the IDX during 2019-2020. Employing a quantitative approach, this research utilizes secondary data sourced from companies' annual financial reports. A purposive sampling method was applied, resulting in a sample of 8 companies. Multiple linear regression analysis was used as the data analysis technique. The findings indicate that taxes and company size have a partial influence on transfer pricing. Conversely, tunneling incentives, bonus mechanisms, and exchange rates do not exhibit a significant impact on transfer pricing individually. However, when considered together, taxes, tunneling incentives, bonus mechanisms, company size, and exchange rates collectively influence transfer pricing.